ALT neuroblastoma chemoresistance due to telomere dysfunction-induced ATM activation is reversible with ATM inhibitor AZD0156 - Koneru, Balakrishna; Farooqi, Ahsan; Nguyen, Thinh H; Chen, Wan Hsi; Hindle, Ashly; Eslinger, Cody; Makena, Monish Ram; Burrow, Trevor A; Wilson, Joanne; Smith, Aaron; Pilla Reddy, Venkatesh; Cadogan, Elaine; et al. (Science translational medicine, 2021)
Cancers overcome replicative immortality by activating either telomerase or an alternative lengthening of telomeres (ALT) mechanism. ALT occurs in ~25% of high-risk neuroblastomas, and progression in patients with ALT neuroblastoma during or after front-line therapy is frequent and often fatal. Temozolomide + irinotecan is commonly used as salvage therapy for neuroblastoma. Patient-derived cell lines and xenografts established from patients with relapsed ALT neuroblastoma demonstrated de novo resistance to temozolomide + irinotecan [SN-38 in vitro, < 0.05; in vivo mouse event-free survival (EFS), < 0.0001] vs. telomerase-positive neuroblastomas. We observed that ALT neuroblastoma cells manifested constitutive ataxia-telangiectasia mutated (ATM) activation due to spontaneous telomere dysfunction which was not observed in telomerase-positive neuroblastoma cells. We demonstrated that induction of telomere dysfunction resulted in ATM activation that, in turn, conferred resistance to temozolomide + SN-38 (4.2-fold change in IC , < 0.001). ATM knockdown (shRNA) or inhibition using a clinical-stage small-molecule inhibitor (AZD0156) reversed resistance to temozolomide + irinotecan in ALT neuroblastoma cell lines in vitro ( < 0.001) and in four ALT xenografts in vivo (EFS, < 0.0001). AZD0156 showed modest to no enhancement of temozolomide + irinotecan activity in telomerase-positive neuroblastoma cell lines and xenografts. Ataxia telangiectasia and Rad3 related (ATR) inhibition using AZD6738 did not enhance temozolomide + SN-38 activity in ALT neuroblastoma cells. Thus, ALT neuroblastoma chemotherapy resistance occurs via ATM activation and is reversible with ATM inhibitor AZD0156. Combining AZD0156 with temozolomide + irinotecan warrants clinical testing for neuroblastoma.